Jurists’ training in Spain today - Quintero Olivares, Gonzalo (EUNOMÍA. Revista en Cultura de la Legalidad, 2022)
The formation of the young jurist in Spain is deficient. The cause is not in the unfortunate and almost unfeasible Bologna Plan, but it is earlier, and it is not reduced to one. Pre-university training in humanities is almost non-existent. There is an excess of Faculties of Law and centers that teach Law, with which improvised teachers abound, and, with this, the student’s training is often superficial, to which is added the little interest in the legal works. The introduction of national tests to access the attorney profession, in which the Bar Associations have an excessive weight, has not remedied the situation.